Molecularly imprinted polymer composites as sensor - Mortari, Bianca [UNESP] (2020)
Molecularly imprinted polymers (MIPs) are defined as nanomaterials with sensitive and selective properties. The detection property of different molecules by applying different analytical methods makes the MIPs highly attractive. These polymers offer an alternative approach to recognition when compared to biological systems such as proteins and enzymes since they have a small size, high surface area, greater stability, robustness, and resistance in different extremal conditions (temperature and pH) to biological recognition. Recently, molecular imprinting with a biomimetic sensor has proved a substitute method in environmental research for the recognition of various targeted elements. Usually, MIP and hybrid-MIP are immobilized on the surface of the electrode by electropolymerization process, magnetization using an immobilized magnet on the sensor surface, an immobilizer for fix the MIP or mixing with other materials to obtain a composite. MIP sensors based in optical and electrochemical transduction attracted great interest from researchers since they are potentially sensitive, selective, low cost and have been widely used for detecting diverse analytes of interest.